The Role of Safety Leadership in Shaping Safety Culture: The Mediating Role of Communication and Commitment - Farhan , Akmal; Ambarwati, Rita; Dedy (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study aims to link safety leadership to safety culture and safety climate as intermediaries. The research method used is a survey. Statistical analysis used to test the hypothesis with SEM-PLS, a sample of 317 was taken with a saturated sampling technique and used second-order data processing. The results of the study indicate a positive correlation between safety leadership and safety culture and safety climate. The conclusion of this study is that safety leadership plays a role in shaping safety climate and maintaining safety culture in the workplace. This research is important because cultivating a positive safety climate and culture can lead to reduced accidents in the workplace, higher employee morale, and overall organizational performance.